2006
DOI: 10.1095/biolreprod.106.053512
|View full text |Cite
|
Sign up to set email alerts
|

Adenylate Kinases 1 and 2 Are Part of the Accessory Structures in the Mouse Sperm Flagellum1

Abstract: Proper sperm function depends on adequate ATP levels. In the mammalian flagellum, ATP is generated in the midpiece by oxidative respiration and in the principal piece by glycolysis. In locations where ATP is rapidly utilized or produced, adenylate kinases (AKs) maintain a constant adenylate energy charge by interconverting stoichiometric amounts of ATP and AMP with two ADP molecules. We previously identified adenylate kinase 1 and 2 (AK1 and AK2) by mass spectrometry as part of a mouse SDS-insoluble flagellar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
62
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 39 publications
(50 reference statements)
3
62
0
Order By: Relevance
“…However, there were not positive signals on immature spermatozoa. Mitochondrial respiration in the midpiece is a significant source of ATP required for mammalian sperm motility, 30 but only by diffusion to other regions of the tail or by active transport along the flagellum can mitochondrial ATP be used for sperm motility. However, the diffusion of ATP to the principal piece is restricted because of the long flagellum of the mammalian spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were not positive signals on immature spermatozoa. Mitochondrial respiration in the midpiece is a significant source of ATP required for mammalian sperm motility, 30 but only by diffusion to other regions of the tail or by active transport along the flagellum can mitochondrial ATP be used for sperm motility. However, the diffusion of ATP to the principal piece is restricted because of the long flagellum of the mammalian spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…ATP is used by the dynein ATPases that function as the flagellar motors and in protein kinase A-mediated signal transduction pathways to regulate motility throughout the tail (Cao et al, 2006). In the mouse sperm, Mukai and Okuno (2004) reported that glycolysis has an important role in providing the ATP required for mouse sperm motility than mitochondrial respiration throughout the length of the flagellum.…”
Section: Freezability Of Rat Sperm Induced By Raffinose In Modified Kmentioning
confidence: 99%
“…AK activity is necessary for ATP synthesis and to maintain an adequate concentration of ATP in eukaryotic cells. 4) It is reasonable that the expression of RGD1303144 and ODF1 is up-regulated in 7-week-old rat testis during the sexual maturation process.…”
mentioning
confidence: 94%
“…Recently, AK1 and AK2 have been explored, including their expression in a maturing mouse testis. 4) These genes are expressed differentially and buffer the adenylate energy charge to produce adequate sperm motility. Taken together, an ATP energy supply and the elastic ODF protein structure are essential requirements for sperm flagellum movement.…”
mentioning
confidence: 99%
See 1 more Smart Citation